rancang bangun mesin pemecah kemiri dengan metode lempar untuk meningkatkan produktivitas dengan kapasitas 20kg/jam: rancang bangun mesin pemecah kemiri dengan metode lempar untuk meningkatkan produktivitas dengan kapasitas 20kg/jam - Sastra Afriansa; Mietra Anggara; Amri Hidayat; Afrianto (Hexagon, 2025)
In general, the process of cracking candlenuts still uses a manual process with rattan bags and hit on stones, so it requires a lot of manpower with special skills. The method used in this study is the throwing system. Based on the results of the study, the results of the rotor test with an average test using 3 rpm variations. Where using 800 rpm obtained intact results with a value of 24.39%, split in half 21.13%, crushed 4.87% and not broken 44.71%. Then with the use of 1000 rpm obtained intact results with a value of 28.45%, split in half 19.51%, crushed 4.06% and not broken 41.46%. While the use of 1200 rpm can produce intact cores 27.23%, split in half 18.29%, crushed 16.26% and not broken 32.52%. So in the test with the rotor using 3 rpm variations (800,100, and 1200) the results of the intact core were obtained with a rotation of 1200 rpm with a result of 27.23%. So by using the designed candlenut nut cracker, the production capacity of the cracker is able to break with a capacity of up to 20 kg / hour.